I hate you more - Gilmore, Lucy (Romance fiction writer) (Sourcebooks Casablanca, 2021)
"Best in Show meets The Hating Game in this sweet, funny rom-com that takes the uber-competitiveness of dog show pageant moms to a whole new level. Ruby Taylor thought her days of high-stakes competition were over, until she joins the dog show circuit to get lazy golden retriever Wheezy into shape...and falls head over heels for a handsome veterinarian who won't stop getting under her skin"--